Legal Protection of the Exclusive Rights of Painting Works - Lindawati Putri Widharta; Elvira Fitriyani Pakpahan; Tommy Leonard; Teguh Prasetyo (Institut Seni Indonesia Yogyakarta, 2023)
The purpose of this study is to examine how artists’ exclusive rights are protected by law. The empirical legal method was used for the research. The study found that if a law or regulation regulates the protection of a creation’s exclusive rights, it is certain that there will also be legal remedies for violations of the problem of using other people’s creations without permission. These legal remedies can be taken in either litigation or non-litigation. If the effort is made through litigation, namely by filing a lawsuit to the commercial court or can be prosecuted criminally, this is already included in the Copyright Law, or by a resolving. In light of the conversation above with respect to legitimate security of the select privileges of makers of compositions, the public authority ought to have the option to make sense of additional explicitly in the items in the Intellectual property Regulation in regards to canvases that poor person has been made sense of top to bottom, and there ought to be more effort to the public so that individuals are all the more endlessly figure out the presence of lawful security for work or creation. Perlindungan Hukum Hak Eksklusif Karya Lukis. Tujuan dari penelitian ini adalah untuk mengkaji bagaimana hak eksklusif seniman dilindungi oleh hukum. Metode hukum empiris digunakan untuk penelitian ini. Kajian ini menemukan bahwa jika suatu peraturan perundang-undangan mengatur tentang perlindungan terhadap hak eksklusif suatu ciptaan, maka dapat dipastikan juga akan ada upaya hukum atas pelanggaran terhadap masalah penggunaan ciptaan orang lain tanpa izin. Upaya hukum ini dapat ditempuh baik secara litigasi maupun non litigasi. Apabila upaya tersebut dilakukan melalui litigasi, yaitu dengan mengajukan gugatan ke pengadilan niaga atau dapat dituntut secara pidana, hal tersebut sudah termasuk dalam Undang-Undang Hak Cipta, atau dengan cara penyelesaian. Sehubungan dengan percakapan di atas sehubungan dengan keamanan yang sah dari hak pilih pembuat komposisi, otoritas publik harus memiliki pilihan untuk menjelaskan secara lebih eksplisit dalam item dalam Peraturan Kekayaan Intelektual tentang kanvas yang dibuat oleh orang miskin. dimaklumi dari atas ke bawah, dan harus ada upaya yang lebih kepada masyarakat agar setiap individu semakin mengetahui adanya jaminan hukum atas suatu karya atau ciptaan.